Pathological Consideration of Hypothyroidism in Ayurvedic Classics (International Journal of Ayurveda and Pharma Research, 2023)
Ayurveda considers diseases are the consequence of Doshavaisamya i.e., the imbalance of body humours and health is the state of their equilibrium. Even though hypothyroidism is not directly mentioned in Ayurveda, it can be addressed because Ayurveda doesn't emphasize on naming the disease rather it emphasis on proper understanding of the Prakruti, Koshta, Dosha, Dhatu, Mala and Agni status of the patient and treat accordingly. Nowadays, hypothyroidism is a common issue encountered in our OPDs. Hypothyroidism has to be carefully addressed as it can lead to other lifestyle disorders like dyslipidemia, coronary artery diseases, hypertension and chronic inflammatory diseases like arthritis. Since the thyroid gland is involved in the metabolic functions of body, its hormonal actions can be correlated to the functions of various levels of Agni.This article is an attempt to conceptualize hypothyroidism in terms of Ayurvedic pathophysiology to facilitate further understanding and to provide better treatment options.